KEVALIDAN BUKU AJAR ENSIKLOPEDIA BERBASIS POTENSI LOKAL PADA SUB MATERI INVERTEBRATA KELAS X MIA - Imamatus Sholihah; St Syamsudduha; Zulkarnaim Zulkarnaim (Al-AHYA: Jurnal Pendidikan Biologi, 2021)
This study aims to develop a valid encyclopedia textbook based on local potential on Invertebrate sub-material which is valid, which can be used as a reference for students in the Class X MIA Invertebrate sub-material. The encyclopedia developed is in the form of a textbook that discusses Invertebrate material combined with local potential in Takalar Regency in the form of the sea, the pictures in the encyclopedia developed are original images obtained from the results of Bioecological sampling using the LIT (Line Intercept Transcet) technique. This type of research is a type 4-D development research developed by S Thiagarajan, Dorothy S, Semmel, and Melvyn I Semmel, this type of development consists of 4 stages, the first stage is Define, the second stage is design, the third stage development, and the fourth stage of dissemination, but the research carried out by researchers only reached the validation level development stage, because the Covid-19 pandemic situation did not allow researchers to carry out trials and the deployment stage in the field.